Małe analizy. Etiudy w PWSFTviT - Kolski, Jan Jakub (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2012)
Little tiny analysis. Etudes in The Polish National Film, Television and Theatre School Performing as a lecturer and artistic tutor of students’ etudes requires creation of a common platform for discussion and constructive criticism. The above text is an example of didactic pact between the teacher and the student. Analysis of the Rafał Skalski etude Żeby nie było niczego is also an excuse to discuss the composition, construction of the characters and acting roles, as well as so-called "Zatorski spiral", interpretation of ‘becoming’ and truth in dialogue. Discussed scenes of the etude allow to understand the importance of internal tension – a kind of punctum – creating a dramatic and visual potential of the film.